Annual Plan West Bengal 1997-98 Volume-II - Planning Commission (Planning Commission, 1997)
Draft Annual Plan : 1997-98—Proposed Outlay, Physical Targets and Achievements, Draft Annual Plan (1997-98)—Proposals for Spillover and On-going Programmes/Projects as in Annexure-I : A-l Completed Schemes as on 31.3.1996 A-2. Schemes Completed during 1995-96 & Likely to be Completed during 1996-97, (Spillover liability, if any. for 1997-98 and beyond), A-3. Critical On-going Schemes (as on 31.3.1997), IIIB Draft Annual Plan (1997-98)—Proposals for Maximising Benefits of Completed Programmes/Projects (as on 31.3.1997), IIIC Draft Annual Plan (1997-98)—Proposals for Programmes/ Projects—New Schemes.
Development and Planning Department